2009
DOI: 10.1038/ismej.2009.65
|View full text |Cite
|
Sign up to set email alerts
|

Specific rhizosphere bacterial and fungal groups respond differently to elevated atmospheric CO2

Abstract: Soil community responses to increased atmospheric CO 2 concentrations are expected to occur mostly through interactions with changing vegetation patterns and plant physiology. To gain insight into the effects of elevated atmospheric CO 2 on the composition and functioning of microbial communities in the rhizosphere, Carex arenaria (a non-mycorrhizal plant species) and Festuca rubra (a mycorrhizal plant species) were grown under defined atmospheric conditions with either ambient (350 p.p.m.) or elevated (700 p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 75 publications
1
47
1
Order By: Relevance
“…Our first hypothesis was that elevated CO 2 and increased N avail- Our results do not support this hypothesis and showed that there was no significant effect of elevated CO 2 or N amendment on the overall bacterial community structure and diversity. This is consistent with results from previous studies showing no effect of elevated CO 2 on overall bacterial community composition, richness, and total abundance (1,8,22,44,78), although some studies reported significant changes in specific bacterial groups such as deltaproteobacteria (8), heterotrophic decomposers (29,44), rhizosphere colonizers (12), and ammonia-oxidizing bacteria (32). Our results are further supported by the finding at the same site that overall ectomycorrhizal fungal richness and diversity were not affected by elevated CO 2 (64).…”
Section: Discussionsupporting
confidence: 92%
“…Our first hypothesis was that elevated CO 2 and increased N avail- Our results do not support this hypothesis and showed that there was no significant effect of elevated CO 2 or N amendment on the overall bacterial community structure and diversity. This is consistent with results from previous studies showing no effect of elevated CO 2 on overall bacterial community composition, richness, and total abundance (1,8,22,44,78), although some studies reported significant changes in specific bacterial groups such as deltaproteobacteria (8), heterotrophic decomposers (29,44), rhizosphere colonizers (12), and ammonia-oxidizing bacteria (32). Our results are further supported by the finding at the same site that overall ectomycorrhizal fungal richness and diversity were not affected by elevated CO 2 (64).…”
Section: Discussionsupporting
confidence: 92%
“…As consequences, increased carbon input in turn significantly changed bacterial diversity, composition, and structure and increased the functional potential of bacterial communities for carbon degradation and nutrient cycling, although such effects differed across various ecosystems (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast, fungal biomass and relative abundance of total microbial biomass did not change significantly under eCO 2 in this BioCON (biodiversity, CO 2 , and N deposition) experimental site (6,21).…”
mentioning
confidence: 72%
“…In contrast, fungal biomass and relative abundance of total microbial biomass did not change significantly under eCO 2 in this BioCON (biodiversity, CO 2 , and N deposition) experimental site (6,21). Previous studies of fungal responses to eCO 2 were mainly carried out using approaches such as phospholipid fatty-acid analysis, denaturing gradient gel electrophoresis, extracellular enzyme assays, and clone library analysis (6,12,16,(21)(22)(23) and mostly focused on mycorrhizal fungi (15,(24)(25)(26), which have major influences on plant biodiversity and productivity (27). Those previous studies were focused on fungal carbon degradation, nitrogen cycling, and interactions with plants (26,28,29); however, knowledge about fungal community-level responses to eCO 2 is still limited, though some efforts have been made recently (12,30,31).…”
mentioning
confidence: 83%
“…Yet, a four-year exposure to CO 2 in a FACE experiment site decreased the abundance of archaea but did not affect the population size of soil bacteria under trembling aspen (Lesaulnier et al, 2008). It was believed that elevated CO 2 increased plant photosynthetic rate and productivity, and the increase in the above-ground photosynthesis will result in greater below-ground C allocation via root exudation and rhizodeposition (Hungate et al, 1997;Jackson et al, 2009;Palmroth et al, 2006;Phillips et al, 2006), which can directly stimulate changes in the size and community structure of soil microorganisms (Drigo et al, 2009). However, no significant difference in DOC between ambient CO 2 and elevated CO 2 was observed in this study which was partly in consistent with the study of Jackson et al (2009), who found that no significant change of DOC between ambient and elevated CO 2 condition in the O horizon of soil.…”
Section: Responses Of Soil Bacterial and Archaeal Abundance To Elevatmentioning
confidence: 99%